Genetic and biochemical characterization of an Escherichia coli K-12 mutant deficient in acyl-coenzyme A thioesterase II. - Narasimhan, M L (1986)
Mutants of Escherichia coli deficient in thioesterase II activity were isolated by taking advantage of the fact that thioesterase I specifically hydrolyzes long-chain (C12 to C18) acyl coenzyme A (CoA) esters but is unable to cleave the short-chain substrate decanoyl-CoA. One of these lesions (designated tesB1) reduces thioesterase II activity to about 10% of the normal level. The mutant enzyme activity was abnormally labile to temperature, but it was normal in all the other characteristics examined (pH optimum, Km for decanoyl-CoA, molecular weight). The level of thioesterase I activity was unaffected by the tesB1 lesion. The tesB locus was mapped with a closely linked Tn10 insertion. tesB was mapped to minute 10 of the E. coli linkage map, close to the lon locus. The clockwise gene order is lon tesB acrA dnaZ. The tesB mutation is recessive. We found no phenotype for the mutation. The fatty acid compositions of the phospholipids, lipid A, and lipoprotein components are normal in thioesterase II mutants. These data show that thioesterases I and II of E. coli are encoded by different genetic loci and strongly suggest that tesB is the structural gene for thioesterase II.